A review of the South Pacific Manota Williston (Diptera, Mycetophilidae), with the description of thirteen new species - Kurina, Olavi; Hippa, Heikki (Zootaxa, 2015)
The genus Manota is found to consist of 37 species in the South Pacific region. The following 13 species are described as new: M. acris sp. n. (Papua New Guinea (PNG)), M. alulata sp. n. (PNG), M. apentachaeta sp. n. (PNG), M. clivicola sp. n. (PNG), M. cordata sp. n. (PNG), M. feminea sp. n. (PNG), M. kaindiensis sp. n. (PNG), M. lunata sp. n. (PNG), M. nimia sp. n. (Solomon Is.), M. pentachaeta sp. n. (PNG), M. siciliculata sp. n. (PNG), M. sigma sp. n. (PNG) and M. unisetata sp. n. (Solomon Is.). New records of the following 11 species are presented: M. bicuspis Hippa, 2007 (PNG, Solomon Is.), M. biunculata Hippa, 2007 (PNG), M. evexa Hippa, 2007 (PNG), M. explicans Hippa, 2007 (PNG), M. hamulata Colless, 1966 (PNG), M. pacifica Edwards, 1928 (Samoa), M. parilis Hippa, 2007 (PNG, Vanuatu), M. perissochaeta Hippa, 2007 (PNG), M. serawei Hippa, 2007 (PNG), M. spathula Hippa, 2007 (PNG) and M. subspathula Hippa, 2007 (Australia). The latter is the first described species of Manota recorded from continental Australia. A redescription of M. pacifica Edwards, 1928 is given.